2021
DOI: 10.1007/s11740-021-01022-w
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to tailored forming

Abstract: In recent years, the requirements for technical components have been increasing steadily. This development is intensified by the desire for products with lower weight, smaller size and extended functionality, but at the same time higher resistance against specific loads. Mono-material components manufactured according to established processes reach their limits regarding conflicting requirements. It is, for example, hardly possible to combine excellent mechanical properties with lightweight construction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Thus, the stresses occurring in the material during forming can be modified. In particular, critical tensile stresses in the area of the joining zone can be reduced in this way [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the stresses occurring in the material during forming can be modified. In particular, critical tensile stresses in the area of the joining zone can be reduced in this way [4].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Tailored Forming is an innovative method for the production of hybrid components. In this process, pre-joined hybrid semi-finished parts are used, which offers the possibility of using simple semifinished part geometries and modifying the joining zone thermomechanical with regard to its geometry during the process [4]. Furthermore, different well-established joining processes like laser beam welding, laser, plasma powder welding or rotary friction welding can be applied depending on the used materials and application.…”
Section: Introductionmentioning
confidence: 99%
“…Innerhalb des Sonderforschungsbereichs (SFB) 1153 wird die Prozesskette zur Herstellung hybrider Hochleistungsbauteile durch Tailored Forming erforscht, um ressourceneffizienten Leichtbau mittels lokal angepasster Eigenschaften von Massivbauteilen umzusetzen [11]. So bilden die anfallenden Forschungsdaten und zugehörigen Prozessbeschreibungen die Grundlage für die relevante Prozesskettenentwicklung und im Falle der Zugversuche für die Entwicklung von Materialmodellen der hybriden Bauteile.…”
Section: Forschungsdatenmanagement-systemunclassified
“…They found that the precipitation hardened state of aluminium alloys are more suited for processing than the soft annealed state if the intention is to obtain a sound bonding behaviour with steel. An innovative manufacturing route for the production of hybrid components named Tailored Forming was developed using hybrid pre-joined semifinished [4]. The material combination of steel and aluminium has great potential for industrial application in hybrid components.…”
Section: Introductionmentioning
confidence: 99%